2011
DOI: 10.1007/s13178-011-0063-0
|View full text |Cite
|
Sign up to set email alerts
|

“We’d Be Free”: Narratives of Life Without Homophobia, Racism, or Sexism

Abstract: Stigma and social inequality deprive disadvantaged social groups of a sense of social well-being. Stress researchers have focused on prejudice-related events and conditions but have not described more intangible stressors experienced by sexual minorities. We use narrative methods to examine how sexual minorities experience stigma and social inequality as we focus on the more intangible stressors that are both pervasive and difficult to measure. Three themes emerged in the narratives of our ethnically diverse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 23 publications
5
83
0
Order By: Relevance
“…Likewise, culture and religion have also been explored as resiliencies. These factors may be very important for YBGBM, as studies have shown Black MSM to draw upon positive associations with Black and gay identities in response to stigma (Meyer, Ouellette, Haile & McFarlane, 2011) and engage in religious-focused coping in response to life stressors (Pitt, 2010;Woodyard, Peterson & Stokes, 2000). Second, we took a compensatory or main effects view of resilience in this study, in that we aimed to see how different forms of resilience were related to psychosocial factors.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, culture and religion have also been explored as resiliencies. These factors may be very important for YBGBM, as studies have shown Black MSM to draw upon positive associations with Black and gay identities in response to stigma (Meyer, Ouellette, Haile & McFarlane, 2011) and engage in religious-focused coping in response to life stressors (Pitt, 2010;Woodyard, Peterson & Stokes, 2000). Second, we took a compensatory or main effects view of resilience in this study, in that we aimed to see how different forms of resilience were related to psychosocial factors.…”
Section: Discussionmentioning
confidence: 99%
“…More recent research has identified non-event stressors-or stress that results from denial of opportunities and hoped for accomplishments that do not come to pass-as an additional source of minority stress given sexual minority individuals are more often blocked from achieving their life goals that heterosexuals because of their stigmatized status (Frost & LeBlanc, 2014;Frost, 2011;Meyer & Dean, 1998;Meyer, Ouellette, Haile, & McFarlane, 2011;Pearlin, 1999).…”
mentioning
confidence: 99%
“…Narrative research also has the potential to illustrate what effect social policy change may have on LGB lives (Meyer et al 2011). For example, Meyer et al (2011) employed narrative methods to investigate what the lives of sexual minority individuals would be like without homophobia, heterosexism, and discrimination.…”
Section: Narrative Research and Social Justicementioning
confidence: 99%
“…For example, Meyer et al (2011) employed narrative methods to investigate what the lives of sexual minority individuals would be like without homophobia, heterosexism, and discrimination. Likely impossible to study with quantitative survey methods, asking about what this experience would look like highlights the need for policy interventions by demonstrating the potential outcomes of policy change and providing interventionists with clear goals.…”
Section: Narrative Research and Social Justicementioning
confidence: 99%
See 1 more Smart Citation